Foreign direct investment and cities
1 online resource (336 pages)
Keywords: Presenting a rich collection of insights into investment by foreign corporations into different types of cities around the world, Foreign Direct Investment and Cities uses original and revelatory case studies to help readers to turn theory into practice.The book offers a structured set of case study chapters, with a diversity of location, setting, and industry, focus on macro-, meso-, and micro-level factors, and outcomes in economic and non-economic terms. The chapters are authored by a diverse collection of international experts. The text is also supported by digital learning resources, including PowerPoint slides and video clips.Foreign Direct Investment and Cities will be relevant to courses in international business and economic geography and will be key reading for academic researchers in business schools and wider social sciences, as well as the global practitioner community in investment promotion.